Pengadaan Bidak Baca untuk Memperkuat Kemampuan Literasi Siswa SD Inpres 138 Matawolot - Adi Iwan Hermawan; Abdul Hafid; Rima Rima; Siti Fatihaturrahmah Al Jumroh; Kartika Tiara Syarifuddin; Selfiani Selfiani (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service activity aims to improve elementary school students' literacy skills through the provision of innovative learning media,